Comparative Evaluation of Intrathecal Administration of Levobupivacaine (Hyperbaric) Alone and Low-Dose Levobupivacaine (Hyperbaric) in Combination with Fentanyl in Lower Limb Surgeries: A Prospective Randomized Controlled Trial - Sangma, Salomi A; Singh, Vishawjeet; Jamwal, Shyamli; Sharma, Shalini; Sharma, Manjula (National Journal of Medical Research, 2025)
Background: Spinal anaesthesia is a preferred method for lower limb surgeries. Levobupivacaine, an S-enantiomer of bupivacaine, is associated with fewer cardiotoxic effects. Fentanyl, an opioid adjuvant, may enhance the efficacy of local anaesthetics. The purpose was to compare the efficacy and safety of intrathecal hyperbaric levobupivacaine alone versus low-dose levobupivacaine with fentanyl in lower limb surgeries. Methodology: Eighty ASA I-II patients undergoing elective lower limb surgeries were randomly divided into two groups. Group L received 15 mg hyperbaric levobupivacaine; Group LF received 12.5 mg levobupivacaine with 25 µg fentanyl intrathecally. Sensory/motor block characteristics, haemodynamic stability, and side effects were assessed. Results: The onset of sensory block was faster in Group L (2.86 ± 0.97 min) than Group LF (3.42 ± 0.96 min) (p = 0.011). Sensory block lasted slightly longer in Group LF (102.37 ± 17.72 min vs. 96.88 ± 27.85 min; p = 0.305). Motor block durations were comparable (p = 0.952). Haemodynamic parameters remained stable and similar between groups. Side effects, including hypotension and bradycardia, were slightly more frequent in Group L, but not statistically significant. Conclusion: Both regimens are effective and safe. Levobupivacaine alone provides faster onset, while the addition of fentanyl permits dose reduction without compromising efficacy. The combination is a clinically useful alternative for lower limb surgeries with minimal side effects.